Pelatihan Membaca Kitab Arab untuk Anak Usia Sekolah di Desa Linggarsari - Novinsyah, Indra; Prasetiadi, Yan Septiana; N, Nurhaimin (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The ability to read Arabic texts is a fundamental skill in Islamic education for school-aged children. However, learning practices that emphasize memorization and oral repetition often result in low independent reading skills. This community service program aims to improve children’s Arabic reading ability in Linggarsari Village through habit-based reading training. The methods included initial observation, guided reading practice focusing on letters and diacritics, gradual reading exercises, and evaluation. The results indicate improvements in reading accuracy, confidence, and reduced reliance on memorization. This program contributes to strengthening Arabic literacy and community-based religious education.